2016
DOI: 10.3174/ajnr.a5010
|View full text |Cite
|
Sign up to set email alerts
|

Collar Sign in Incompletely Occluded Aneurysms after Pipeline Embolization: Evaluation with Angiography and Optical Coherence Tomography

Abstract: The collar sign appears to be indicative of endothelialization, but continued blood flow into the aneurysm. This is unusual given the processes involved in aneurysm occlusion after placement of the Pipeline Embolization Device and has not been previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…The 2 main principles on which the concept was founded are diversion of blood flow away from the aneurysm inducing stasis and thrombosis within the aneurysm sac and endothelialization along the stent scaffold and restoration of the integrity of the arterial wall. 8 These devices have effectively addressed the issue of recanalization and the need for retreatment associated with other endovascular treatment modalities and are continuously gaining popularity among neurointerventionalists. 9 Whereas treatment of internal carotid artery aneurysms up to the superior hypophyseal segment provided an early experience with flow diverters, 1 use has since expanded to a number of different aneurysm locations.…”
Section: Aneurysm Characteristics In Eufredmentioning
confidence: 99%
“…The 2 main principles on which the concept was founded are diversion of blood flow away from the aneurysm inducing stasis and thrombosis within the aneurysm sac and endothelialization along the stent scaffold and restoration of the integrity of the arterial wall. 8 These devices have effectively addressed the issue of recanalization and the need for retreatment associated with other endovascular treatment modalities and are continuously gaining popularity among neurointerventionalists. 9 Whereas treatment of internal carotid artery aneurysms up to the superior hypophyseal segment provided an early experience with flow diverters, 1 use has since expanded to a number of different aneurysm locations.…”
Section: Aneurysm Characteristics In Eufredmentioning
confidence: 99%
“…Following exclusion of duplicate and irrelevant references and after detailed abstract and title screening, 10 references directly relating to endothelialization were included per the search criteria (On-line Table). [5][6][7][8][9][10][11][12][13][14] Two of the included references studied endothelialization in human patients. 7,14 The remainder of the included articles used preclinical animal models, constituting pigs (n ϭ 1) and rabbits (n ϭ 7).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work by our group has demonstrated the angiographic appearance of separation of the parent vessel from aneurysms following PED placement, termed the "collar sign," in incompletely occluded aneurysms. 7 We have hypothesized that this represents endothelialization along the stent surface in juxtaposition to the aneurysmal neck. Paradoxical incomplete aneurysm occlusion following PED placement at 6-month follow-up may be po- tentially explained via the existence of interspersed channels between regions of neointimal hyperplasia, still allowing blood flow, corroborated by a case report by Dai et al 30 Similarly, endothelialization has been shown to be a driving factor in determining aneurysmal exclusion in intracranial aneurysms treated by coil embolization.…”
Section: Mechanisms Of Aneurysm Occlusion: Human Datamentioning
confidence: 99%
“…44 The "collar sign" is visualized as an interval in opacification of contrast between the parent vessel and aneurysm sac on angiography and is thought to represent the endothelialization process across the neck of the aneurysm. Failure of proper endothelialization process can lead to unsecured aneurysms and ruptures.…”
Section: Mechanism: Endothelializationmentioning
confidence: 99%
“…Griessenauer et al coined the term "collar sign" to describe the radiographic pattern of incompletely occluded aneurysms of patients who underwent PED placement. 44 The "collar sign" is visualized as an interval in opacification of contrast between the parent vessel and aneurysm sac on angiography and is thought to represent the endothelialization process across the neck of the aneurysm. Here, they found that 50% of patients who had incompletely occluded aneurysms (10.5%) at their 6-month follow-up also had the "collar sign."…”
Section: Mechanism: Endothelializationmentioning
confidence: 99%